“A study on factors that influence employee engagement at Heitech Managed Services Sdn Bhd” / Nadhirah Yusreen Mohd Nasruddin - Mohd Nasruddin, Nadhirah Yusreen (Faculty of Business and Management, 2014)
Engaging right employees with their right behaviours are the critical aspect faced by organization today. This engagement starts when a firm able to find, understand and manage those talented workers and strive to maintain it into a higher level of engagement. High level of employee engagement may guarantee not only the short term survival of a firm but also the factor for a long term business performance. Nevertheless, for employees act to be an engaged workers, neither employers not only prioritized on what they should do to ensure them to be engaged but employees are also eligible to say their wants in making them to be such accordance employees. The purpose that the researcher wanted to conduct this study is mainly to know the factors that would made employees to be engaged in the organization, thus, able to retaining them for a long period of time. Apart from that, if the employees were said to be engaged, employers strive to keep it into a higher level, meaning that to ensure the employees would contribute towards high performance for the benefits of themselves and the organization. This study was conducted at HeiTech Managed Services Sdn. Bhd whereby the population are the employees. It has 170 targeted employees, however only 130 employees were selected as the sample size and it was based on the probability of Simple Random Sampling. Unfortunately, out of 130, only 100 respondents managed to return back the questionnaires to the researcher. This study found out that those three independent variables which are working environment, working relationship and career development had a relationship with employee engagement. Nevertheless, working environment is the most influence factor of employee engagement in this study.